Identificación y prospección de nematodos en el Sistema agroforestal en el campus Salache, cantón Latacunga, provincia de Cotopaxi, 2022-2023. - Toapanta Quevedo, Kevin Ismael (2023)
The identification and prospection of nematodes is fundamental to know the species and number of nematodes that exist in the Agroforestry System located in the campus Salache Canton Latacunga Province of Cotopaxi. Samples were collected in different lots at different depths: 5cm, 10cm and 15cm, for this the Zig Zag method was implemented, using an auger, the samples were placed in a cover where a composite sample was obtained from each depth, a total of 12 soil samples were collected and then taken to the laboratory, where we proceeded to perform the extraction of nematodes, therefore 100g of soil was weighed for each sample, then they were homogenized, sieved, centrifuged and observed under the microscope. At a depth of 5 cm, Scutellonema sp was found with 57 individuals, Meloidogyne sp with 24 individuals and Helicotylenchus sp with 12 individuals. At a depth of 10 cm, Scutellonema sp was found with 42 individuals, Meloidogyne sp with 8 individuals and Helicotylenchus sp with 9 individuals. At a depth of 15 cm, Scutellonema sp was found with 53 individuals, Meloidogyne sp with 9 individuals and Helicotylenchus sp with 16 individuals. Thus, the improvement of soil fertility with the incorporation of plant material increases the microbial flora, allowing biological control between the different species of microorganisms, which is why it was found that the species of nematodes present did not affect the established crops.